Metode Latihan Dengan Bermain Gerak Untuk Meningkatkan Kemampuan Menari Tarian Tradisional Anak Usia 5-6 Tahun - Diah Andika Sari; Indah Juniasih (JCE (Journal of Childhood Education), 2025)
Traditional dance is a dance that has certain rules that are passed down from generation to generation. To introduce Indonesian traditional dance to children, a fun training method is needed during training. This study aimed to improve children's traditional dance dancing skills through the dance training method with Playing Movement used during dance training. The study was conducted on 10 children, at Budi Mulia Kindergarten, South Tangerang. This study used the Classroom Action Research (CAR) Model Kemis Taggart method. The instruments for the ability to dance traditional dances for children aged 5-6 years in this assessment are: 1) Ability to move to the rhythm of the music; 2) Balance of body movements; 3) Coordination of body movements; 4) Ability to perform dance movement forms; 5) Ability to follow dance movements completely; 6) Flexibility; and 7) Ability to express oneself while dancing. The training activities were carried out 10 times, for 4 weeks. The Play Movement Training method was used at the beginning of the training, or as a warm-up, and at the end of the training or cooling down. During the observation in the pre-cycle, the average ability of children was at the 28% stage, at the undeveloped stage. After training using the Movement Play Exercise method for 3 meetings in cycle 1, it increased to 49%, still at the beginning of development stage. In cycle 2, it increased to 65%, which was at the development stage according to expectations. In cycle 3, it increased to 89%, which was at the very well-developed stage. So it can be concluded that the Movement Play Exercise method can improve the ability to dance traditional dances of children aged 5-6 years at Budi Mulia Kindergarten, South Tangerang.